Address Terms Used in Discount Account Found in Instagram - Giyatmi, Giyatmi -; Astuti, Purwani Indri (HUMANIKA, 2023)
Addressing the customer is one way to attract the interest of the customers as well as to build intimacy with them. This study aims at describing the types of address terms used in discount account in Instagram. This research is classified as a descriptive qualitative research because it observes the address terms used by discount account in Instagram.  The data of the study are the address terms found in discount accounts in Instagram. The writers use three account discounts in Instagram such as; @giladiskonn https://www.instagram.com/giladiskonn/#, @diskondijogja https://www.instagram.com/diskondijogja/, @info_diskon https://www.instagram.com/info_diskon/. To collect the data, the writers use documentation. The technic of data analysis consists of four steps such as data collection, data reduction, data display, and conclusion. The research found 37 address terms used by discount accounts in Instagram. Next, they are distributed into 4 types of address terms, namely Kinship address term (5), Pet name/nickname/special nick name (23), pronoun (2), and slang address term (7). Pet names/nicknames/special nicknames are the most dominant address terms used in discount accounts. The use of pet name/nicknames/special nicknames includes pet name with product names, pet names with company names, pet names with brands, pet names with account names. Pet name address terms are used to show close relation between buyers and sellers which is important in running online business. Meanwhile, the least address terms used in discount account is pronoun.